Targeting of scavenger receptors Stabilin-1 and Stabilin-2 ameliorates atherosclerosis by a plasma proteome switch mediating monocyte/macrophage suppression - Manta, Calin-Petru; Leibing, Thomas; Friedrich, Mirco; Nolte, Hendrik; Adrian, Monica; Schledzewski, Kai; Krzistetzko, Jessica; Kirkamm, Christof; Schmid, Christian David; Xi, Yannick; Stojanovic, Ana; Tonack, Sarah; et al. (Circulation, 2022)
Background: - Scavenger receptors Stabilin-1 (Stab1) and Stabilin-2 (Stab2) are preferentially expressed by liver sinusoidal endothelial cells. They mediate the clearance of circulating plasma molecules controlling distant organ homeostasis. Studies suggest that Stab1 and Stab2 may affect atherosclerosis. Although subsets of tissue macrophages also express Stab1, hematopoietic Stab1 deficiency does not modulate atherogenesis. Here, we comprehensively studied how targeting Stab1 and Stab2 affects atherosclerosis. - Methods: - ApoE-KO mice were interbred with Stab1-KO and Stab2-KO mice and fed a Western diet. For antibody targeting, Ldlr-KO mice were also used. Unbiased plasma proteomics were performed and independently confirmed. Ligand binding studies comprised glutathione-S-transferase-pulldown and endocytosis assays. Plasma proteome effects on monocytes were studied by single-cell RNA sequencing in vivo, and by gene expression analyses of Stabilin ligand-stimulated and plasma-stimulated bone marrow-derived monocytes/macrophages in vitro. - Results: - Spontaneous and Western diet-associated atherogenesis was significantly reduced in ApoE-Stab1-KO and ApoE-Stab2-KO mice. Similarly, inhibition of Stab1 or Stab2 by monoclonal antibodies significantly reduced Western diet-associated atherosclerosis in ApoE-KO and Ldlr-KO mice. Although neither plasma lipid levels nor circulating immune cell numbers were decisively altered, plasma proteomics revealed a switch in the plasma proteome, consisting of 231 dysregulated proteins comparing wildtype with Stab1/2-single and Stab1/2-double KO, and of 41 proteins comparing ApoE-, ApoE-Stab1-, and ApoE-Stab2-KO. Among this broad spectrum of common, but also disparate scavenger receptor ligand candidates, periostin, reelin, and TGFBi (transforming growth factor, β-induced), known to modulate atherosclerosis, were independently confirmed as novel circulating ligands of Stab1/2. Single-cell RNA sequencing of circulating myeloid cells of ApoE-, ApoE-Stab1-, and ApoE-Stab2-KO mice showed transcriptomic alterations in patrolling (Ccr2-/Cx3cr1++/Ly6Clo) and inflammatory (Ccr2+/Cx3cr1+/Ly6Chi) monocytes, including downregulation of proatherogenic transcription factor Egr1. In wildtype bone marrow-derived monocytes/macrophages, ligand exposure alone did not alter Egr1 expression in vitro. However, exposure to plasma from ApoE-Stab1-KO and ApoE-Stab2-KO mice showed a reverted proatherogenic macrophage activation compared with ApoE-KO plasma, including downregulation of Egr1 in vitro. - Conclusions: - Inhibition of Stab1/Stab2 mediates an anti-inflammatory switch in the plasma proteome, including direct Stabilin ligands. The altered plasma proteome suppresses both patrolling and inflammatory monocytes and, thus, systemically protects against atherogenesis. Altogether, anti-Stab1- and anti-Stab2-targeted therapies provide a novel approach for the future treatment of atherosclerosis.
Ursprünglich veröffentlicht: 3. November 2022
Gesehen am 02.09.2024